Strategies and Best Practices in Social Innovation An Institutional Perspective (Springer International Publishing, 2018)
This book examines the different ways companies can develop and design social innovation. Combining technological and social perspectives, the contributors present emerging research on social innovation from different sectors such as entrepreneurship, education and energy. Collectively, the authors demonstrate the ways in which social innovation can drive sustainability and development in regions around the world. All societies are characterized by their political, economic and social institutions, as well as by how they utilize technology. The social innovations with the highest importance are those which modify existing institutions or create new ones, and based on their magnitude, they can be considered as radical or incremental. For example, when Joseph Chamberlain encouraged workers to organize in order to achieve universal male suffrage in Great Britain in 1885, this was a considered a radical innovation for British society, which in turn changed its political framework. Social innovations may be based on intelligence and commitment, on technology or on social entrepreneurship in its most open forms. In addition, social innovations can be classified into those which correspond to an entire country or region, a field (e.g., education) or a sector (e.g., entrepreneurship, technology, social reform). Featuring contributions on topics such as agro-food, smart cities, higher education, gender equality and sports, this book is ideal for academics, students, scholars, professionals and policy makers in the areas of innovation, entrepreneurship, sustainability and regional development.